Exploring The Lecturers’ Needs of Lms-Based Instruction At The English Department - Noni, Nurdin; Sakkir, Geminastiti; Jefri, Riny (Seminar Nasional LP2M UNM, 2023)
Abstract. This study focuses on the use of learning management system (LMS) as a web-based application that can be used by lecturers to manage and organize their courses, i.e. planning, implementing, evaluating, and giving feedback certain learning processes. This research aims at finding out the needs of English lecturers in implementing LMS-based online instruction. This research uses descriptive qualitative method. The respondents consist of the lecturers of the English Department of Universitas Negeri Makassar who have teaching experiences using LMS application in delivering their courses. The instrument used is a set of interview guide. The data collected through interview were analyzed through transcribing, classifying, and interpreting. The results of this study indicate that the lecturers need comprehensive training to understand the LMS features better. They believe this training will help them optimize the use of LMS in their teaching. In addition, increasing internet capacity and availability of hardware and software is needed. The development of interactive learning content through LMS is also considered important. In addition, institutional policies that support LMS use also play an important role. It ca be concluded that training, better technological infrastructure, and collaboration between lecturers are needed to effectively utilize LMS in their instruction.   Key words: LMS-based instruction, lecturer’s need, English language learning